(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Salinity intrusion in coastal regions of Bangladesh is a growing concern due to its potential impact on public health, particularly reproductive health among women. Exposure to saline water may contribute to a variety of health challenges, including menstrual irregularities and pregnancy complications. Objective This study aimed to assess the reproductive health challenges faced by women in salinity-affected areas and compare these findings with women living in non-salinity-affected areas in Bangladesh. Methods A cross-sectional comparative study was conducted among 647 married women of reproductive age (15–49 years), with 405 participants from salinity-affected areas and 242 from non-salinityaffected areas. Data were collected using a pretested structured questionnaire and face-to-face interviews. Water samples from the study areas were tested for salinity and other parameters, including pH, electrical conductivity (EC), total dissolved solids (TDS), and sodium (Na). Statistical analyses included chi-square tests, ordinal logistic regression, and the Mann-Whitney U test, with a significance level set at p < 0.05. Results Women in salinity-affected areas exhibited significantly higher rates of reproductive health issues, including irregular menstrual cycles (42.5% vs. 27.3%, p < 0.01), genital itching (38.2% vs. 18.6%, p < 0.001), and lower abdominal pain (35.4% vs. 20.2%, p < 0.001). Pregnancy complications were more prevalent in salinityaffected areas (48.6% vs. 32.4%, p < 0.01). Water quality analysis revealed higher salinity (4.5±1.3 ppt vs. 0.6±0.2 ppt, p < 0.001) and elevated sodium levels in the affected areas. Conclusion Salinity-affected areas in Bangladesh show a higher burden of reproductive health challenges among women, which may be linked to poor water quality. Effective interventions, including water treatment and community health education, are essential to mitigate these health risks. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 784-796